Integrated Management of ADHD: A Multimodal Review of Pharmacological, Psychosocial, Digital, and Lifestyle Interventions - Vankayala, Phanindra; Vankayala, Radhakrishna; Gumudavelli, Sridhar; Gumudavelli, Sricharan; Kumar, S Sathish (European Journal of Applied Sciences, 2025)
Attention Deficit/Hyperactivity Disorder (ADHD) is a chronic neurodevelopmental condition characterized by inattention, hyperactivity, and impulsivity, affecting both children and adults. While stimulant medications remain the first-line treatment due to their rapid and robust symptom control, they often fall short in addressing functional impairments related to executive functioning, emotional regulation, and social skills. This review explores a comprehensive spectrum of interventions for ADHD management, encompassing pharmacological, formulation-based, psychosocial, neurocognitive, digital, and lifestyle approaches. Pharmacological therapies, including both stimulants and nonstimulants, have strong short-term efficacy, and advances in drug formulations such as extended-release, transdermal, and prodrug preparations have improved adherence, reduced abuse potential, and enabled time-specific symptom control. Psychosocial and behavioral therapies, such as Cognitive Behavioural Therapy (CBT), parent training, and mindfulness-based interventions, address emotional and executive challenges and enhance overall functioning. Neurocognitive and digital interventions, including neurofeedback, cognitive training, and FDA-approved digital therapeutics like EndeavorRx, offer scalable and engaging options targeting attention and cognitive control. Lifestyle strategies such as aerobic exercise, diet quality, micronutrient supplementation, and gut microbiome modulation serve as supportive or adjunctive tools with growing empirical support. The integration of these strategies into personalized, multimodal treatment plans has shown superior outcomes compared to monotherapies. This review underscores the importance of tailoring interventions based on individual needs, preferences, and developmental context, and highlights the need for ongoing research to optimize long-term care in ADHD.